2017
DOI: 10.1038/ismej.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Linking the community structure of arbuscular mycorrhizal fungi and plants: a story of interdependence?

Abstract: Arbuscular mycorrhizal fungi (AMF) are crucial to plants and vice versa, but little is known about the factors linking the community structure of the two groups. We investigated the association between AMF and the plant community structure in the nearest neighborhood of Festuca brevipila in a semiarid grassland with steep environmental gradients, using high-throughput sequencing of the Glomeromycotina (former Glomeromycota). We focused on the Passenger, Driver and Habitat hypotheses: (i) plant communities driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 59 publications
(1 reference statement)
8
61
0
1
Order By: Relevance
“…P. recta and R. serotine , Figure ). Spatial distance can be a major factor in shaping AM fungal communities in roots in a similar spatial scale used in this study (Horn et al, ; Maherali & Klironomos, ), and dispersal limitation of AM fungi can be a dominant mechanism behind this observation (Vályi et al, ). This apparent dispersal inability can cause AM fungal community to structure at scales of <1 m (Mummey & Rillig, ).…”
Section: Discussionmentioning
confidence: 76%
“…P. recta and R. serotine , Figure ). Spatial distance can be a major factor in shaping AM fungal communities in roots in a similar spatial scale used in this study (Horn et al, ; Maherali & Klironomos, ), and dispersal limitation of AM fungi can be a dominant mechanism behind this observation (Vályi et al, ). This apparent dispersal inability can cause AM fungal community to structure at scales of <1 m (Mummey & Rillig, ).…”
Section: Discussionmentioning
confidence: 76%
“…Findings from Horn et al . () and Hiiesalu et al . () indicate that plant–fungal interactions at least partly drive covariation of plant and AM fungal communities.…”
Section: Introductionmentioning
confidence: 84%
“…() and Horn et al . () recorded correlation between plant and AM fungal community composition in different ecosystems. Context‐dependent effects of AM fungi on plants (Hoeksema et al ., ) suggest that the relatedness of plant and AM fungal communities might change in response to shifts in the biotic or abiotic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies show that host plants influence AM fungal community assembly, the authors did not evaluate the influence of the plant community structure (but a few selected plant species), nor the role of the AM fungi in determining the plant community structure. Another study evaluating relationships between communities found that plant composition influenced AM fungal community composition in soil but not vice versa, and that this effect was weak after accounting for spatial effects (Horn, Hempel, Verbruggen, Rillig, & Caruso, ). However, this study used indirect approaches to estimate the strength and significance of relationships, which are accurate only if the major pattern of variation in the predictor community is also important for the response community (Ter Braak & Schaffers, ).…”
Section: Discussionmentioning
confidence: 99%